Diagnosis and treatment of carcinoma in situ (non-invasive atypical epithelium) - Blanchard, Oscar (2015)
The injury in question has numerous designations or names as varied descriptions. We believe that the designation "carcinoma in situ" or "intraepithelial carcinoma" or "superficial" or "preinfiltrativo" are incongruous to call "carcinoma" to a state that does not have its specific characteristics, nor will we know whether, namely proliferation active atypical, invasive or destructive, and metastasize. Indeed, it is histopathological lesions and therefore is necessary to fix the designation and description.